Individualism, Human Capital Formation, and Labor Market Success - Katharina Hartinger; Sven Resnjanskij; Jens Ruhose; Simon Wiederhold (Center for Economic Studies and ifo Institute (CESifo), 2021)
There is an ongoing debate about the economic effects of individualism. We establish that individualism leads to better educational and labor market outcomes. Using data from the largest international adult skill assessment, we identify the effects of individualism by exploiting variation between migrants at the origin country, origin language, and person level. Migrants from more individualistic cultures have higher cognitive skills and larger skill gains over time. They also invest more in their skills over the life-cycle, as they acquire more years of schooling and are more likely to participate in adult education activities. In fact, individualism is more important in explaining adult skill formation than any other cultural trait that has been emphasized in previous literature. In the labor market, more individualistic migrants earn higher wages and are less often unemployed. We show that our results cannot be explained by selective migration or omitted origin-country variables.
Keywords: D91; J24; I20; Z13; 330; cognitive skills; culture; individualism; labor market; international comparisons